Smart packaging with carotenoids: a breakthrough in food quality and preservation - Abu Bakar, Ainaa Eliah; Othman, Rashidi (Nova Science Publishers, Inc., 2026)
The use of intelligent packaging, which can assess the freshness of packed food in real-time and display the packaging film’s colour change based on the condition of the food, has grown in popularity recently. In all fields of life sciences, the trend towards sustainability, enhanced product safety, and high standards of quality are significant. A cutting edge technology called intelligent packaging food indicator helps to assure food safety and quality while preventing food contamination. With intelligent packaging, food freshness and quality changes may be tracked in real time. One of the most well-known natural colourants, carotenoids, has drawn a lot of interest due to its good functional qualities and capacity to alter colour in response to pH variations. Biomaterials rich in carotenoid have many biological benefits, including anticancer, antibacterial, antiviral, and antioxidant qualities. They are also inexpensive and readily available. Carotenoid’s functional qualities have been extensively utilised in the development of intelligent packaging solutions. This is because colour is omnipresent by nature and has the power to communicate important information about food packing. the potential use of carotenoid as a health-promoting, intelligent packaging indication.